Feasibility Analysis of Solar-Powered Tubewells in Arid and Sub-humid Regions of Rajasthan - Priyanka Upreti,; Dharam Raj Singh2,; Nalini Ranjan Kumar,; P. Venkatesh,; Manjeet Singh Nain,; Girish Kumar Jha,; Suresh Kumar, (Indian Journal of Extension Education, 2023)
The study analysed the investment and returns of installing solar-powered pumps, besides their economic feasibility and efficiency in arid and sub-humid regions of Rajasthan based on primary data collected for the year 2018-19. The feasibility analysis while accounting for different climatic regions of Rajasthan is imperative to examine since it influences the depth of water table and required power to extract groundwater which would, affect economic feasibility of pumps. Only subsidised investment in solarpowered tubewells was found to be economically feasible in both regions. The efficiencies of solar-irrigated farms and savings in cost after installing solar-powered pumps were found to be higher for sub-humid region, which may be attributed to better utilisation of solar pumps, cultivation of high-value vegetables and adoption of improved technologies. The major constraint faced by farmers in adoption of solar-powered pumps in arid region was found to be their non-functioning in higher water table situations, while in sub-humid region, it was a high initial investment. Hence, there is need to have custom-made policies according to climatic regions of the country and to increase awareness regarding benefits of adoption of advanced technologies and high-value crops which can complement the benefits of adoption of solar-powered pumps.